(untitled) (Journal of Contemporary Philology, 2022)
In this paper we will present the theory of symbolic capital within the field of literature by the French theorist, sociologist and anthropologist Pierre Bourdieu, mainly elaborated in his book on the topic of literature entitled Rules of Art (1992) and his numerous essays on the same topic. We will present and analyze his theory of symbolic capital in two ways: first by itself, as explained in his books and essays; and then through various examples from the world of literature. In the first part we will present the conversation between the American writers Ernest Hemingway and Scott Fitzgerald about the nature of writing, described by Hemingway in the book A Movable Feast. In the second and third part we will move on to the presentation and analysis of the concept of symbolic capital. Firstly, we will define the term and analyze and place Bourdieu’s definitions in a broader context; then we will talk about the specific manifestations of symbolic capital in the field of literature and its relationship with classical, i.e. economic capital in the narrow sense of the word; we will also talk about the genesis of this notion, on an individual and social level; while at the end we will talk about its possible transformations into economic capital. In the conclusion we will draw general observations regarding what was presented in this paper, and the contribution of Bourdieu’s theory to the study of literature.